HUBUNGAN MOTIVASI BELAJAR, DISIPLIN BELAJAR, DAN AKTIVITAS BELAJAR DENGAN HASIL BELAJAR DALAM PEMBELAJARAN TEMATIK - Nabilah, Hariani Nisa; Asrori, Muhammad; Sulistyarini, Sulistyarini (Universitas Tanjungpura, 2023)
This study aims to describe the relationship between in learning motivation, learning discipline, and learning activity with the students learning achievement in the thematic lesson. This study used a quantitative approach with correlation research type. The sample of this amounted to 27 students. Data collection was carried out using a questionnaire and documentation study. The analysis technique was carried out by using determine the relationship between in learning motivation, learning discipline, and learning activity on the students